Scott Pilgrim vs. the world [videorecording (Blu-Ray)] - Wright, Edgar, 1974-; Bacall, Michael; Pope, Bill, 1952-; Godrich, Nigel; Cera, Michael; Winstead, Mary Elizabeth; Culkin, Kieran; Evans, Chris, 1981-; Kendrick, Anna; Larson, Brie, 1989-; Pill, Alison, 1985-; Plaza, Aubrey, 1984-; et al. (Universal Studios, 2019)
"Scott Pilgrim just met the girl of his dreams ... literally. But in order for them to date, he must defeat her seven evil ees - a rogues' gallery incluidng an infamous skateboarder, a vegan rock star and fearsome identical twins." -- Container.